Running : a complete guide - Kupris, Bronnie Storch (Dell Publishing Co., 1978)
From starting out to marathon running all the basics of this exhilarating, fast-paced sport! Learn about running techniques. warmup exercises, proper gear, the mental and physical benefits of running, and more!